2021
DOI: 10.1029/2021gl093127
|View full text |Cite
|
Sign up to set email alerts
|

No Cryosphere‐Confined Aquifer Below InSight on Mars

Abstract: Large volumes of water are hypothesized to have carved and passed through the Martian outflow channels (e.g., Baker, 2001). Because these channels originate from discrete sources, a groundwater origin is typically invoked (e.g., Head et al., 2003). Given the large discharges needed to create the observed landforms, in some cases a couple orders of magnitude greater than the largest catastrophic floods on Earth (Baker, 1982), large and permeable aquifers would be needed (e.g., Carr, 1979;Manga, 2004). While mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…This is indicated by the observation that the granular and fractured media models predict velocities that are too high for fully ice-saturated sediments and basalt. Manga and Wright (2021) drew a similar conclusion for the upper 8 km of crust because their modeled V s for an ice-saturated basalt was high compared to measured V s . It is unlikely that we misinterpreted a basalt layer for an ice-saturated sediment layer; the predicted V p for the Amazonian and/ or Hesperian basalt layer matches, but V s is overpredicted by at least 0.5-2.3 km/s (Figures 1 and 2).…”
Section: Fractured Basalt Layers With Up To 20% Of Its Pores Filled W...mentioning
confidence: 64%
See 2 more Smart Citations
“…This is indicated by the observation that the granular and fractured media models predict velocities that are too high for fully ice-saturated sediments and basalt. Manga and Wright (2021) drew a similar conclusion for the upper 8 km of crust because their modeled V s for an ice-saturated basalt was high compared to measured V s . It is unlikely that we misinterpreted a basalt layer for an ice-saturated sediment layer; the predicted V p for the Amazonian and/ or Hesperian basalt layer matches, but V s is overpredicted by at least 0.5-2.3 km/s (Figures 1 and 2).…”
Section: Fractured Basalt Layers With Up To 20% Of Its Pores Filled W...mentioning
confidence: 64%
“…This is indicated by the observation that the granular and fractured media models predict velocities that are too high for fully ice-saturated sediments and basalt. Manga & Wright (2021) drew a similar conclusion for the upper 8 km of crust because their modeled V s for an ice-saturated basalt was low compared to measured V s .…”
Section: Fractured Basalt Layers With Up To 20% Of Its Pores Filled W...mentioning
confidence: 68%
See 1 more Smart Citation
“…V s are 1.7-2.1 km/s in the upper crust (i.e., between 0 km and ∼8-11 km) and 2-3.4 km/s in the deeper crust (i.e., between ∼8-11 km and 20 km) (Figure 1). Interpretations using self-consistent fractured-media rock physics models Berryman, 1980) indicate that V s within the upper 8-11 km is lower than expected for a cryosphere (Manga & Wright, 2021;Wright et al, 2022). V s between 11 km and 20 km may be consistent with basalts whose fractures are 1-5% filled with calcite cement (Manga & Wright, 2021).…”
Section: Introductionmentioning
confidence: 90%
“…Below this transition zone, a sequence of high and low velocity layers found by the Rayleigh wave ellipticity inversion for the topmost 200 m is interpreted as a sequence of lava flows inter-fingered with a sedimentary unit. Manga and Wright (2021) have concluded that the seismic velocities in the top 10 km underneath InSight are too low to suggest an ice-saturated cryosphere.…”
Section: Seismic Observations Of the Hammeringmentioning
confidence: 99%